Bypass authentication detection in information system databases using intelligent enterprise architecture solution - Kopp, Andrii Mykhailovych; Orlovskyi, Dmytro Leonidovych; Olkhovyi, Oleksii Mykhailovych (Громадська наукова організація "Всеукраїнська асамблея докторів наук з державного управління", 2025)
The relevance of the study is explained by the high prevalence of SQL injection attacks, which violate the confidentiality, integrity, and availability of data, as well as allow bypass authentication attempts in information system databases. The considered problem is architecture-centric by its nature, as the vulnerability of a single information system module can compromise the entire enterprise system. In addition, SQL injections put at risk information security compliance and business process execution stability. The object of research includes the process of bypass authentication detection in information system databases. The subject of research includes the intelligent enterprise architecture solution used for bypass authentication attempts detection in information system databases. The research aims to the development of an intelligent enterprise architecture solution for securing information system databases by detecting bypass authentication attempts based on the comprehensive use of machine learning classification algorithms. In this study, the intelligent solution for detecting SQL injections with bypass authentication attempts was developed and proposed to be integrated into the enterprise architecture landscape. A machine learning-based software component based on six classification algorithms (single-layer perceptron, logistic regression, k-NN, SVM, naïve Bayes, and decision trees) was proposed. An experimental evaluation was conducted based on a largest Kaggle dataset of SQL queries, by comparing their classification performance and computational efficiency. The research results allowed to identify the most effective algorithms for the further implementation, especially in real-time information system databases. Актуальність дослідження пояснюється високою поширеністю таких атак, як SQL-ін’єкції, що порушують конфіденційність, цілісність і доступність даних, а також дозволяють робити спроби обходу автентифікації в базах даних інформаційних систем. Розглянута проблема за своєю природою є архітектурно-орієнтованою, оскільки вразливість одного модуля інформаційної системи може поставити під загрозу всю корпоративну систему. Крім того, SQL-ін’єкції ставлять під загрозу дотримання вимог інформаційної безпеки та стабільність виконання бізнес-процесів. Об’єктом дослідження є процес виявлення обходу автентифікації в базах даних інформаційних систем. Предметом дослідження є інтелектуальне рішення для архітектури підприємства, яке використовується для виявлення спроб обходу автентифікації в базах даних інформаційних систем. Дослідження має на меті розробку інтелектуального рішення для архітектури підприємства з метою захисту баз даних інформаційних систем шляхом виявлення спроб обходу автентифікації на основі комплексного використання алгоритмів класифікації машинного навчання. У цьому дослідженні було розроблено інтелектуальне рішення для виявлення SQL-ін’єкцій із спробами обходів автентифікації та запропоновано його інтеграцію в архітектуру підприємства. Було запропоновано програмний компонент на основі машинного навчання, який базується на шести алгоритмах класифікації (одношаровий перцептрон, логістична регресія, k-NN, SVM, наївний Байєс та дерева рішень). Було проведено експериментальну оцінку на основі найбільшого набору даних Kaggle із SQL-запитами, порівнявши їхню ефективність класифікації та обчислювальну ефективність. Результати дослідження дозволили визначити найефективніші алгоритми для подальшого впровадження, особливо в базах даних інформаційних систем реального часу.
Keywords: bypass authentication detection; information system; database; intelligent software solution; enterprise architecture; обхід автентифікації; інформаційна система; база даних; інтелектуальне програмне рішення; архітектура підприємства